Austria : Financial Sector Assessment Program Update Technical Note; Factual Update and Analysis of the IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This technical note focuses on the International Organization of Securities Commissions objectives and principles of securities regulations of Austria. The 2003 assessment found that Austria had fully broadly implemented a large majority of principles. The human resources of the Securities Supervision Department of the Financial Market Authority (FMA) should be increased, especially to conduct on-site inspections, in addition to the 14 planned appointments. Administrative fines should be raised further to levels elsewhere in Europe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet